2002
DOI: 10.1128/iai.70.4.1924-1935.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Various Enterotoxins in Aeromonas hydrophila- Induced Gastroenteritis: Generation of Enterotoxin Gene-Deficient Mutants and Evaluation of Their Enterotoxic Activity

Abstract: Three enterotoxins from the Aeromonas hydrophila diarrheal isolate SSU have been molecularly characterized in our laboratory. One of these enterotoxins is cytotoxic in nature, whereas the other two are cytotonic enterotoxins, one of them heat labile and the other heat stable. Earlier, by developing an isogenic mutant, we demonstrated the role of a cytotoxic enterotoxin in causing systemic infection in mice. In the present study, we evaluated the role of these three enterotoxins in evoking diarrhea in a murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
207
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(219 citation statements)
references
References 43 publications
9
207
0
3
Order By: Relevance
“…Aeromonas species produces an array of virulence factors, one of the most significant of which is a 52-kDa cytotoxic enterotoxin (Act) (49), which possesses several biological activities, including hemolysis, cytotoxicity, enterotoxicity and lethality to mice, and induced acute inflammatory response both in vitro and in vivo (50). In vitro, Act activates mitogen-activated protein kinase (MAPK) pathways and classical caspase-associated apoptosis in intestinal epithelial cells and macrophages (51)(52)(53). In addition, a recent study showed that with intramuscular bacterial inoculation in mice, A. hydrophila could recruit inflammatory cells around the inoculation site earlier than E. coli and K. pneumonia, and elicit a specific pathological change, myonecrosis (54).…”
Section: Discussionmentioning
confidence: 99%
“…Aeromonas species produces an array of virulence factors, one of the most significant of which is a 52-kDa cytotoxic enterotoxin (Act) (49), which possesses several biological activities, including hemolysis, cytotoxicity, enterotoxicity and lethality to mice, and induced acute inflammatory response both in vitro and in vivo (50). In vitro, Act activates mitogen-activated protein kinase (MAPK) pathways and classical caspase-associated apoptosis in intestinal epithelial cells and macrophages (51)(52)(53). In addition, a recent study showed that with intramuscular bacterial inoculation in mice, A. hydrophila could recruit inflammatory cells around the inoculation site earlier than E. coli and K. pneumonia, and elicit a specific pathological change, myonecrosis (54).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate Pic activity on intestinal mucin in vivo, the rat ligated ileal loop model was used (9,42,48). Sprague-Dawley rats (n Ï­ 4) of either sex and between 70 and 100 g in weight were used.…”
Section: Methodsmentioning
confidence: 99%
“…(Aguilera-Arreola et al, 2007). A correlation between the higher number of toxin genes harboured in an isolate of Aeromonas and its potential to induce diarrhea have been earlier reported (Sha et al, 2002;Chang et al, 2008) and their detection in food products is very essential. The results of the present study indicated that the detection and identification of toxigenic Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Exotoxins are major virulence factors of Aeromonas spp. that include a cytotoxic heat-labile enterotoxin (Act), also known as aerolysin/hemolysin (Chopra et al, 1993); a cytotonic heat-labile enterotoxin (Alt), also known as lipase, extracellular lipase, or phospholipase (Chopra et al, 1996); and a cytotonic heat-stable enterotoxin (Ast) (Sha et al, 2002). These toxins are encoded by the genes act, alt and ast, respectively (Sen and Rodgers, 2004).…”
Section: Introductionmentioning
confidence: 99%